WHY IS THE IMPLEMENTATION OF GOOD ENVIRONMENTAL GOVERNANCE ESSENTIAL? (A SYSTEMATIC LITERATURE STUDY) - Khithobi, Arya Teges; Asmorowati, Sulikah; Hariani, Nurul Jamila (Jurnal Kebijakan Pemerintahan, 2024)
Abstract This study aims to clarify the adverse effects stemming from the absence of Good Environmental Governance (GEG) practices. This investigation employed a methodical approach to review the literature, focusing on nine research articles selected using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. GEG, as a transformative mechanism, holds significant potential for mitigating the effects of global warming. However, in various regions worldwide, numerous individuals continue to struggle with the effective implementation of GEG. Forests represent the areas most adversely affected by the absence of GEG implementation. Numerous environmental challenges persist, including issues related to air quality, water standards, urban waste management, transportation systems, land use, deforestation, and shifts in climate patterns. The absence of GEG implementation manifests in adverse trends such as diminished rule of law, weakened institutional capacity, insufficient community engagement, and a lack of transparency and accountability. This study aspires to serve as a reference for governments in the pressing need to implement GEG, aiming to construct a more sustainable environmental framework that mitigates the effects of global warming. Keywords: Good Environmental Governance, Implementation, PRISMA, Systematic Literature Study.